The Creative City: an Utopia or a model of development ? - Christine Liefooghe (European Regional Science Association (ERSA), 2010)
In a competitive world, nations, regions and cities need new models of development. They often attempt to reproduce the success of the Silicon Valley, the regeneration of Bilbao thanks to the Guggenheim museum, or the emergence of a cultural district as Soho in Manhattan. But what are the secrets of the success ? Researchers try to find an answer, and some of them offer to the stackeholders some models. In an uncertain world, theories and models presented as toolkits for economic development or urban revitalization are appealing to the policy-makers. So the "creative city" model is one of the different urban schemes of development, such as the "technopolitan city" in the 1980s, the more selective "global city" model, the "sustainable city", and the "digital city" focused on Internet technologies. But when they attempt to reproduce one of these models, the stackeholders often forget the historical and geographical context of their region or city. They imagine the future according to an ideal, whatever it is : the model can become an utopia. The thesis of Charles Landry (2000) and Richard Florida (2020) are presented by their authors as toolkits for the future of advanced nations, the Creative City for Urban Innovators on the one hand, the "3 T Theory" on the other hand. The political interest for creativity and its impact on economic and urban development could be questionned through the analytical grid of utopia and ideology (Mannheim, 1929 ; Ricoeur, 1997). The model(s) of the creative city is (are) ambivalent : on the one side, a capitalist interpretation (competitiveness, urban growth, gentrification), on the other side a social model for viable communities (tolerance, identity, cultural democracy, new governance). But it is also possible to compare the "creative city" model(s) to some famous Urban Utopia, such as the vision of A. Huxley, E. Howard, Le Corbusier, or to the sociological analysis of Jane Jacobs (1969). The debate focuses on the role of city centres versus urban peripheries, on the functional city versus diversity of urban functions, and on the efficiency of urban planning in order to create a "creative city".
Keywords: 330